Game-based learning and Breakout as comprehension techniques in solving math problems in Primary Education - Moral-Sánchez, Silvia Natividad; Roldán-Ortiz, Rocio (Pixel, 2021)
The change experienced in society as a result of the pandemic generated by Covid-19 means that education must adapt to ICT methodologies and tools that allow students access to knowledges in two ways: from the classroom and from their home in e-learning modality if necessary. On the other hand, mathematics education has the challenge that primary school students have sufficient and significant training in solving mathematics problems that allows them to function and integrate into society and their daily tasks with total normality without any problems. This proposal aims to make explicit how through a game-based learning methodology and using ICT as a vehicle through digital breakout, pedagogical alternatives can be established that develop mathematical thinking through meaningful experiences. For this, the learning of an experience carried out in primary education will be analyzed, Brunner's experimental method will be used as a starting point for the autonomous learning of students by discovery. All this will show the fundamental role that ICTs play in autonomous, lasting learning and significant of mathematics
Keywords: Matemáticas -- Estudio y enseñanza; Enseñanza primaria; ICT; Didactic mathematics; Digital education; Breakout; Primary education